2015
DOI: 10.1073/pnas.1422822112
|View full text |Cite
|
Sign up to set email alerts
|

Female peers in small work groups enhance women's motivation, verbal participation, and career aspirations in engineering

Abstract: For years, public discourse in science education, technology, and policy-making has focused on the "leaky pipeline" problem: the observation that fewer women than men enter science, technology, engineering, and mathematics fields and more women than men leave. Less attention has focused on experimentally testing solutions to this problem. We report an experiment investigating one solution: we created "microenvironments" (small groups) in engineering with varying proportions of women to identify which environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
178
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(190 citation statements)
references
References 38 publications
6
178
1
5
Order By: Relevance
“…Many engineering environments are subtly unfriendly or sometimes overtly hostile for women (8,9). The numeric scarcity of women (10,11), nonverbal behavior from male colleagues that excludes women from professional conversations (12), use of masculine pronouns to refer to all scientists and engineers (12,13), and the prevalence of sexist jokes (14) all signal to women that they are outsiders who do not belong in engineering (6,15,16). Even in organizations that prioritize diversity, the ideal engineer is implicitly assumed to be male (17), eroding women's belonging and self-efficacy, leading to burnout and attrition (18).…”
mentioning
confidence: 99%
“…Many engineering environments are subtly unfriendly or sometimes overtly hostile for women (8,9). The numeric scarcity of women (10,11), nonverbal behavior from male colleagues that excludes women from professional conversations (12), use of masculine pronouns to refer to all scientists and engineers (12,13), and the prevalence of sexist jokes (14) all signal to women that they are outsiders who do not belong in engineering (6,15,16). Even in organizations that prioritize diversity, the ideal engineer is implicitly assumed to be male (17), eroding women's belonging and self-efficacy, leading to burnout and attrition (18).…”
mentioning
confidence: 99%
“…This gender gap in active participation may be detrimental to all students: it puts female students at risk of diminished learning outcomes compared to male students, and male students may fail to develop organizational and written communication skills important to successful teamwork. In support of these findings, Dasgupta, Scircle and Hunsinger 45 found that female first year engineering students placed on gender-parity and female-majority teams demonstrated less anxiety and increased confidence and engineering aspirations than their counterparts placed on male-majority teams.…”
Section: Social Science Research Relevant To Team Experiences Of Undementioning
confidence: 84%
“…Most studies suggest that small groups provide more opportunity for inclusiveness, particularly in underrepresented groups including women. [7] While this can be implemented in the smaller sections of the Design Practicum course, the larger lectures in the Introduction to Engineering course will be a challenge. One option is to allow small break-out sessions to answer questions posed by the guest speaker during lectures.…”
Section: Inclusive Classroom Strategiesmentioning
confidence: 99%